Պոլինեզիական բառաձեւի կառուցուածքի ճշգրտումներ հայերէն զուգահեռների հետ համեմատութեան միջոցով - Ստեփանեան, Լեյլա (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Описываются трудности определения структуры полинезийской словоформы из-за неопределенности разграничения таких терминов как морфема — слог — корень — слово. Результаты многолетних исследований показывают, что легендарной прародиной полинезийцев является Армянское нагорье, а факты полинезийских языков, в частности рапануйского, имеют значимость первоисточника для армянского языка, так как подлинно отражают лингвистические реалии протоармянского периода. Выявлено, например, что наиболее часто встречающийся слог современного армянского языка, состоящий из трех звуков и заканчивающийся одним согласным (CVC), является результатом закономерного развития сохранившихся в рапануйском языке разнообразных древнейших (CV, CVV, CVCV) морфем. The article describes difficulties in determining the structure of the Polynesian word form due to the uncertainty in the definition of terms such as morpheme—syllable—root—word. It is revealed that a large group of most common syllables of Modern Armenian, consisting of three sounds and ending with a consonant (CVC), is a result of the regular development of various Rapanui morphemes (CV, CVV, CVCV). Conducting a comparative etymological analysis of Rapanui-Armenian commonalities allows to specify the boundaries of the Rapanui morpheme. As the findings demonstrate, some Rapanui words, which are considered mono-root (R), are in fact duo-root (two-morpheme) repetitive compound words and belong to the wordtype (R-R). The final result also reveals a new quadro-root (four-morpheme) word form in Rapanui, with the (R-R-R-R) structure, which has not been differentiated up until now.
Keywords: Բանասիրութիւն; Պոլինեզիական լեզուներ; Ուսումնասիրութիւններ